Cardiac rehabilitation and exercise therapy in the elderly: Should we invest in the aged? - Menezes, Arthur R (Science Press, 2012)
Coronary heart disease (CHD) is the leading cause of death worldwide and becomes increasingly prevalent among patients aged 65 years and older. Elderly patients are at a higher risk for complications and accelerated physical deconditioning after a cardiovascular event, especially compared to their younger counterparts. The last few decades were privy to multiple studies that demonstrated the beneficial effects of cardiac rehabilitation (CR) and exercise therapy on mortality, exercise capacity, psychological risk factors, inflammation, and obesity among patients with CHD. Unfortunately, a significant portion of the available data in this field pertains to younger patients. A viable explanation is that older patients are grossly underrepresented in these programs for multiple reasons starting with the patient and extending to the physician. In this article, we will review the benefits of CR programs among the elderly, as well as some of the barriers that hinder their participation.